Awareness of Creativity and Its Relationship to Speed and Accuracy of Futsal Soccer for Female Students - Mohsen Mohamed Hassan1 , Nidaa Falih Hassan2 , Ali Muhammad Jawad Al-Sayegh3, Hayder Naji Habash Als (Indian Journal of Forensic Medicine & Toxicology, 2020)
Achieving success in the futsal soccer game also depends on the good potential in the accuracy and speedof implementing basic skills through the superior ability to accuracy and speed of passing the soccer (futsal)to the researchers as well as teachers and lecturers in this game within the scope of the lesson in the thirdand fourth stage, there is a weakness in most Female students in basic play skills, including the skill ofhandling, because they need to play to the speed and accuracy of performance and weakness, according tothe researchers ’opinion, lack of training on them requires awareness, thinking, focus and awareness that thegame needs physical and mental effort to master it, which the researchers decided to go into this problem, theresearchers used the curriculum Descriptive Basloubi survey and correlations because it fits with the natureof the research problem. The research community was determined by the students of the fourth stage in theCollege of Physical Education and Sports Science in the effectiveness of football halls for the academicseason 2018-2019 and the number (14) students, which were completely chosen for the experiment, in asimple random way ( Lottery) and by 100%. The researchers used the scale of creating awareness of theresearcher (Wahb Razzaq), where a scale consists of (28) items that the examiner answers according to fivealternatives, which are (always, sometimes, rarely, never) and grades are given (1,2,3,4,5) on Respectively,as the highest score on the scale was (140), the lowest score is (28), the name of the test - receipt, and eitherthe handover pass test toward players - the goal of the test - measuring the speed and accuracy of passingthem - the conclusions are - distinguished students of the Faculty of Physical Education and Sports Scienceat the University of Kufa In the fourth stage, a good reality of awareness and creativity also characterizedby a good reality in the performance and speed of the skill of handling the futsal football. There is a realcorrelation between the awareness of creativity and the speed and accuracy of the skill of handling futsalfootball. The researchers recommend that it is necessary to focus on psychological matters that increase thestudents ’motivation to think and awareness about creativity and help them in achieving self and forming apersonal sporting identity for each of them using encouraging educational methods to develop the skill ofspeed and accuracy of the passing skill of students in the College of Physical Education and Sports Sciencewhile practising practical lessons and performing sports skills Various specials, futsal soccer skills.